Das Partineum. Ein ethnografischer Ort zur Wissens- und Denkstilteilhabe - Eckhardt, Dennis (Zeitschrift für Empirische Kulturwissenschaft, 2025)
The Partineum. An Ethnographic Place for Sharing Knowledge and Thinking Styles Abstract: Ethnological subjects are playing an increasingly important role in the deve‐ lopment and research of technology. They reflexivise technology, above all by revealing the everyday situatedness of technology in interdisciplinary working contexts with the technological sciences. However, the field reality of interdisciplinary technology reflexivisation can pose a number of problems, as shown by the experiences from our own research network on IT security. On the one hand, the research network is too large to be able to interlink all sub-projects with ethnographic mobility across disci‐ plines. On the other hand, in moments of mutual incomprehension, participants tend to overemphasise unsuccessful communication. The article identifies that these pro‐ blems are conceptualised in various states of research. Inter- and transdisciplinarity, co-laboration and ELSI accompanying research (ethical, law and social implications), for example, lack a clear link between reflexivisation and localisation. However, this connection effectively prevents the aforementioned problems, as shown by the positive experiences from the network. The partineum, as a neologism consisting of partici‐ pation and place (-eum), represents this kind of localised technology reflexivisation and is presented in the article. On an abstract level, it functions as a boundary site to which knowledge colleagues can relate due to its underdetermination. On a concrete level, the partineum is localised as a workshop that operationalises the participation in knowledge and thinking style
Keywords: Reflexivisation; Technology Research; Interdisciplinarity; Fields; Cybersecu‐ rity